(untitled) (Sebha University Conference Proceedings, 2024)
This study aims to compare various physiological and biochemical parameters—namely height, weight, vitamin D levels, calcium levels and parathyroid hormone (PTH) levels, between male and female students aged 21 and 22 at the University of Tobruk. By analyzing these parameters, the study seeks to identify any significant differences between genders, which could have implications for health and nutritional recommendations. The results indicated that the mean height of male students was 165.64 ± 1.1 cm, significantly taller than female students, who had a mean height of 159.39 ± 0.82 cm (p-value = 0.000). However, the mean weight difference between males (63.00 ± 1.3 kg) and females (61.30 ± 1.5 kg) was not statistically significant (p-value = 0.424). Regarding biochemical parameters, male students had significantly higher mean vitamin D levels (16.6 ± 1.3 ng/mL) compared to female students (12.75 ± 0.56 ng/mL, p-value = 0.008). Similarly, males had higher mean calcium levels (9.330 ± 0.093 mg/dL) than females (8.946 ± 0.10 mg/dL, p-value = 0.007). The mean phosphorus levels did not show a significant difference between males (3.23 ± 0.23 mg/dL) and females (3.97 ± 0.50 mg/dL, p-value = 0.179), nor did the PTH levels (p-value = 0.976). In conclusion, the study revealed significant gender differences in height, vitamin D, calcium levels, and PHT among the student population at the University of Tobruk. Males were generally taller and had higher levels of certain biochemical. These findings underscore important gender-specific physiological and biochemical differences within this population.